Circulating Levels of Cathelicidin Antimicrobial Peptide (CAMP) Are Affected by Oral Lipid Ingestion - Höpfinger, Alexandra; Karrasch, Thomas; Schäffler, Andreas; Schmid, Andreas; Justus Liebig University Giessen (My University, 2023)
Introduction: Obesity and related diseases are among the main public health issues in the western world. They are thought to be caused by a state of chronic, low-grade inflammation. Cathelicidin antimicrobial peptide (CAMP) was recently discovered to be expressed and secreted by adipocytes. Representing a novel immunomodulatory adipokine, CAMP might play an important role in the complex interaction between metabolism and inflammation. Methods: In a cohort of 80 volunteers, serum samples were collected prior to, and 2 h, 4 h, and 6 h after, oral lipid ingestion. CAMP, fatty acid binding proteins 2 and 4 (FABP-2/-4), and dipeptidylpeptidase-4 (DPP-4) serum concentrations were measured via ELISA. Human Simpson–Golabi–Behmel syndrome (SGBS) adipocytes were treated with free fatty acids, and gene expression levels of CAMP, FABP-4, and DPP-4 were quantified by RT-PCR. Results: The mean base-line CAMP serum concentration was 55.78 ± 29.26 ng/mL, with a range of 10.77–146.24 ng/mL. Interestingly, CAMP serum levels were positively correlated with LDL cholesterol, but negatively correlated with HDL cholesterol and adiponectin. Men exhibited higher CAMP serum concentrations than women, an effect apparently linked to oral contraception in the majority of female participants. In both genders, CAMP serum concentrations significantly decreased in a stepwise manner 4 h and 6 h after oral lipid ingestion. This decline was paralleled by a rise of serum bile acid and triglyceride levels upon lipid ingestion. In human SGBS adipocytes, treatment with free fatty acids did not affect CAMP gene expression, but increased FABP-4 gene expression. Conclusions: In conclusion, systemic levels of the antimicrobial peptide and novel adipokine CAMP are significantly decreased upon oral lipid ingestion. While this decline might be linked to the simultaneous increase in bile acids, the underlying mechanisms remain to be elucidated. Furthermore, CAMP might indicate a putative novel cardiovascular biomarker of both inflammatory and metabolic relevance in metaflammation and adipose inflammation.
Keywords: CAMP; cathelicidin; bile acid; lipid; adipocyte; ddc:610